Literasi Perencanaan Keuangan Syariah Pada Mahasiswa Program Studi Ekonomi Islam UIN Syech M. Djamil Djambek Bukittinggi - Khadijah Ath Thahirah; Indrayeni Indrayeni; Rahmaita Rahmaita; Dedi Fernanda; Rita Srihasnita RC; Maivalinda Maivalinda (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
This Community Service Program aims to provide awareness to the public, especially students, of the importance of planning and managing finances according to sharia. Especially in this day and age, we are faced with various conveniences in spending money, lifestyles are increasingly binding on society so that they can easily fulfill their needs and desires. Debt has become very commonplace. So that all transactions tend to be carried out using the convenience of credit financing which causes a lot of people and even students to be in debt through online loans. This should be an important concern for students so they are not easily snared by the temptation of usury. So, it takes awareness from students to start managing their finances and this starts with personal finance. In this Community Service Program, we will provide an explanation of how to manage personal finances in an Islamic manner and will also provide training on how to prepare daily cash flow reports and personal financial notes.